The role of novel programmed cell death in head and neck squamous cell carcinoma: from mechanisms to potential therapies - Yujie Xi; Yujie Xi; Yujie Xi; Ling Gao; Ling Gao; Ling Gao; Shaming Li; Shaming Li; Kai Sun; Kai Sun; Peishen Chen; Zhen Cai; et al. (Frontiers Media S.A., 2023)
Head and neck squamous cell carcinoma (HNSCC) is a common oral cancer with poor prognosis and for which no targeted therapeutic strategies are currently available. Accumulating evidence has demonstrated that programmed cell death (PCD) is essential in the development of HNSCC as a second messenger. PCD can be categorized into numerous different subroutines: in addition to the two well-known types of apoptosis and autophagy, novel forms of programmed cell death (e.g., necroptosis, pyroptosis, ferroptosis, and NETosis) also serve as key alternatives in tumorigenesis. Cancer cells are not able to avoid all types of cell death simultaneously, since different cell death subroutines follow different regulatory pathways. Herein, we summarize the roles of novel programmed cell death in tumorigenesis and present our interpretations of the molecular mechanisms with a view to the development of further potential therapies.